Do Swiss family physicians prescribe antibiotics in line with national guidelines? A cross-sectional study - Jelena Dunaiceva; Noémie Boillat-Blanco; Danyu Li; Anne Niquille; Arnaud Peytremann; Catherine Plüss-Suard; Yolanda Mueller (Swiss Medical Weekly)
INTRODUCTION: Inappropriate antibiotic prescribing drives antimicrobial resistance. Although the Swiss Society of Infectious Diseases has introduced national guidelines for common infectious diseases starting from 2019, it remains unclear whether family physicians and paediatricians adhere to them and what factors influence their prescriptions. The aims of this study were to assess whether Swiss family physicians and paediatricians make appropriate antibiotic choices in accordance with national guidelines and to identify physician- and patient-related factors associated with the prescribing of not-recommended antibiotic choices for specific indications.